KARAKTERISTIK DEMOGRAFI PASIEN DENGAN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) - Ekaputri, Mersi (Jurnal Kesehatan Saintika Meditory, 2023)
Chronic obstructive pulmonary disease (COPD) is characterized by persistent progressive airflow limitation due to an exaggerated chronic inflammatory response of the airways and parenchyma. Lungs due to harmful gases or particles. COPD is also one of the leading causes of morbidity and mortality worldwide. The aim of the study was to identify the demographic characteristics of patients with COPD. The type of research used is a retrospective descriptive study. The population in this study were all COPD patients in the outpatient room of the Pulmonary Clinic Clinic at the West Sumatra Lung Hospital, the type of sampling used was consecutive sampling. The number of samples is 48. The results showed that the demographic characteristics of the respondents in the study were that the age of the respondents was more elderly (52.10%), the majority sex was male (93.80%), the education of the respondents was mostly elementary school graduates (47.90%), jobs more than half of the respondents work as farmers (64.60%), the majority have suffered from COPD for < 10 years (81.20%) respondents, the majority smoked < 1 pack per day (68.80%) respondents, the majority smoked for ≥ 20 years (91.60%) respondents , the majority of cigarette types use filter cigarettes (68.80). Promotive, preventive and educative efforts are needed to the community through health workers while for the community or individuals themselves with the demographic research on the characteristics of these respondents so that they are self-aware so as to avoid COPD in the future